Cooperative Tracking Control and Regulation for a Class of Multi-agent Systems - Liang, Hongjing; Zhang, Huaguang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on the characteristics of cooperative control problems for general linear multi-agent systems, including formation control, air traffic control, rendezvous, foraging, role assignment, and cooperative search. On this basis and combined with linear system theory, it introduces readers to the cooperative tracking problem for identical continuous-time multi-agent systems under state-coupled dynamics; the cooperative output regulation for heterogeneous multi-agent systems; and the optimal output regulation for model-free multi-agent systems. In closing, the results are extended to multiple leaders, and cooperative containment control for uncertain multi-agent systems is addressed. Given its scope, the book offers an essential reference guide for researchers and designers of multi-agent systems, as well as a valuable resource for upper-level undergraduate and graduate students. .
Introduction -- Output Regulation of State-Coupled Dynamics with Globally Reachable Topologies -- Cooperative Output Regulation of Heterogeneous Continuous-Time Multi-Agent Systems -- Cooperative Tracking Control for High-Order Multi-Agent Systems Based on Reduced-Order Observer -- Distributed Stabilized Region Regulator for Discrete-Time Dynamics -- Optimal Output Regulation for Heterogeneous Multi-Agent Systems -- Cooperative Robust Containment Control for Heterogeneous Networks.
Keywords: Control engineering; Artificial intelligence; Computational intelligence; Telecommunication; Control and Systems Theory; Artificial Intelligence; Computational Intelligence; Communications Engineering, Networks